A Study of Factors Influencing Customer Loyalty on Keretapi Tanah Melayu Intercity Services - Irfah Nazuha, Ayob (2009)
The cost of selling to new customers is much higher than the cost of selling to existing customers. Therefore, it is important for the company to foster customer loyalty. This research is about a study on relationship between factors influencing customer loyalty on KTM Intercity Services. Factors such as corporate image, service quality, customer trust and customer switching cost have been identified in order to investigate whether or not these factors have significant relationship with customer loyalty. The survey is conducted at Arau, Alor Setar , and Sungai Petani Station. The sample size for this study is 250 customers who are also have experience in using KTM Intercity Services. Data obtained using two methods that are primary and secondary data. Respondents are required to answer the questionnaires that include the statements regarding factors influencing customer loyalty on KTM Intercity Services. The data were analyzed and summarized in a readable and easily interpretable form. The Statistical Package for the Social Science (SPSS) version 12.0 has been used to summarize the data. The results are in the form of reliability testing, frequency, cross tabulation and correlation. Based on this research, the result indicates that there are significant relationships between all the factors toward customer loyalty. Based on the mean and standard deviation for each factor, the first rank that gives the highest significant level according to their importance in influencing customer loyalty on KTM Intercity Services is customer trust. It is followed by the second rank is service quality, the third rank is corporate image, and the fourth rank is switching cost.